2018
DOI: 10.1159/000493177
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy Revisited: Hemodialysis Catheter Malposition into the Chest

Abstract: In most situations, central catheters are implanted in the right jugular vein as initial access for hemodialysis. However, after repeated punctures, the proximal vessels become stenosed and thrombosed and misplacement is likely to occur. Correct catheter position in the vein can be easily ascertained with X-ray or cross-sectional CT imaging. In this report, we describe the case of a 77-year-old patient on chronic hemodialysis via catheter due to arteriovenous fistula dysfunction. We placed a cuffed-tunneled he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In this study, the proportion of stent implantation is relatively high, accounting for 7/10 of the total number of cases. The main reason is that these patients have a high degree of occlusion, and venous lumen retraction still occurs after PTA expansion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the proportion of stent implantation is relatively high, accounting for 7/10 of the total number of cases. The main reason is that these patients have a high degree of occlusion, and venous lumen retraction still occurs after PTA expansion [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that, compared to other well-established causes of catheter dysfunctions, such as central venous stenosis, fibrin sheath formation, and thrombus formation, the occurrence of mechanical problems, such as catheter malposition, was relatively low, which is consistent with previous studies ( 21 ). Dysfunction immediately noted after TCC placement is usually caused by mechanical problems, such as catheter malposition or venous perforation, which, albeit rare, can lead to an emergency resulting in high mortality rates ( 11 , 22 ). However, gentle equipment handling and careful fluoroscopic monitoring of the guidewire, dilator, and peel-away sheath placement through Digital Subtraction Angiography (DSA) can avoid this catastrophic event ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, PTA and an appropriate covered stent was deployed. Venous injuries occur less frequently than 1% ( 41 ), however, appropriate and prompt actions are crucial in the initial management of this potentially fatal complication ( 11 , 42 ). This complication is partly due to the large caliber of TCCs, which can lead to severe hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After consulting with cardiologists and surgeons, the catheter was removed with atrial septal defect occluder (BalMedic ® : 6) 2 to avoid cardiac tamponade. Various misplacements and malpositioning have been previously reported, including catheter malpositioning leading to the perforation of large veins and catheter tip migration into the chest, 3 as well as misplacement of a right internal jugular vein HD catheter into the mediastinum. 4 Our case of inadvertent placement of a TCC into the pericardium is rare and, to our knowledge, previously unreported.…”
mentioning
confidence: 99%